Jenis-Jenis Ikan di Sungai Desa Murung Panti Hilir Kecamatan Babirik - Mawaddah Medika Ananda; Meyninda Destiara; Nurul Himmah (Al Kawnu : Science and Local Wisdom Journal, 2022)
This study aims to identify what fish are found in Murung Panti Hilir Village. The type of research carried out is field research, namely research carried out by collecting data in the field. The data collection technique in sampling is purposive sampling, which is used to determine the research location point. While the sampling technique used the Line Transect method in the swamp area of the village of Murung Panti Hilir. Sampling is done by catching fish found using fishing nets or lunta tools. Installation of tools is carried out in the morning and afternoon. Each sample that is brought one by one will be documented at the place where the sample was found. After that, each sample was made into clear plastic and labeled. From the results of the research conducted, there are 12 types of fish in Murung Panti Hilir Village, Babirik District, namely Tapah Fish (Wallago leeri), Tawes Fish (Puntius javanivus), Saluang Batu Fish (Rasbora aurotaenia), Timah-Timah Fish (Panchax-Panchax), Julung-Julung Fish (Zenarchopterus buffoni), Puyau Lamah Fish (Osteochilus vittatus), Papuyu Fish (Anabas tesrudineus), Lais Tembiring Fish (Crytopterus sp.), Kelabau Fish (Osteochilus kelabau), Baung Fish (Macrones nemurus), Sanggaccompani Fish (Macroness nigriceps) ), and Nila Fish (Oreochromis niloticus).